Strategi Adaptasi dan Mitigasi Perubahan Iklim Di Lahan Gambut: Pendekatan Terintegrasi Untuk Ketahanan Lingkungan - Lailal Gusri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Peatlands constitute a critical ecosystem that stores nearly one-third of global soil carbon, yet faces serious degradation threats from drainage, land conversion, and fires. This study examines climate change adaptation and mitigation strategies in peatlands through an integrated approach to enhance environmental resilience. Employing a systematic literature review methodology of recent publications (2020–2026), this research analyzes concepts, implementation practices, and challenges in sustainable peatland management. The findings demonstrate that peatland restoration through rewetting, revegetation, and community-based management can reduce greenhouse gas emissions by up to 800 million tons of CO₂e annually in tropical regions. Indonesia, as the world's largest tropical peatland holder (25 million hectares), plays a strategic role with emission reduction targets of 31.89%–43.20% by 2030 through forest and peatland conservation under the Forestry and Other Land Use (FOLU) Net Sink 2030 strategy. This study recommends strengthening peatland protection policies, investment in paludiculture (sustainable wet farming), empowerment of local communities, and mobilization of carbon-based financing to achieve global climate targets while maintaining ecosystem services and community livelihoods.